2008
DOI: 10.1093/aje/kwn027
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Multivitamin Supplement Use and Risk of Breast Cancer

Abstract: The authors evaluated the association between multivitamin supplement use and breast cancer risk in a completed trial. At baseline (1992-1995), 37,920 US women aged > or =45 years and free of cancer provided detailed information on multivitamin supplement use. During an average of 10 years of follow-up, 1,171 cases of invasive breast cancer were documented. Multivitamin use was not significantly associated with overall risk of breast cancer. Compared with the risk for never users, the multivariable relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…Previous analyses of dietary supplementation with specific dietary micronutrients showed mixed results [3], and recent results from a prospective study do not support an association between dietary multivitamin supplement use and breast cancer risk [43]. In our study, no substantial change of the risk estimates was observed by additional adjustment for supplement use (Supplementary Tables 2, 3).…”
Section: Discussioncontrasting
confidence: 73%
“…Previous analyses of dietary supplementation with specific dietary micronutrients showed mixed results [3], and recent results from a prospective study do not support an association between dietary multivitamin supplement use and breast cancer risk [43]. In our study, no substantial change of the risk estimates was observed by additional adjustment for supplement use (Supplementary Tables 2, 3).…”
Section: Discussioncontrasting
confidence: 73%
“…Only limited support has been found for the hypothesis that vitamin use is associated with breast cancer [19][20][21][22]. The role of individual nutrients in etiology of BRCA-related breast cancer has not been studied extensively, but researchers have recommended that carriers consider a daily supplement regimen containing agents that may ultimately enhance DNA repair since the BRCA gene is involved in DNA damage repair, among other functions [23].…”
Section: Vitamin Usementioning
confidence: 99%
“…In 1998, the United States and Canada mandated the folic acid fortification of foods. Moreover, supplements are a major source of folic acid, and '50% of US adults take multivitamins (15)(16)(17). In one small study, 78% of postmenopausal women had unmetabolized synthetic folate in their blood (18).…”
Section: Introductionmentioning
confidence: 99%